Disclosure of Traditional and Complementary Medicine Use and Its Associated Factors to Medical Doctor in Primary Care Clinics in Kuching Division, Sarawak, Malaysia - Anak Kelak, Johny; Whye, Lian Cheah; Safii, R. (Hindawi Publishing Corporation, 2017)
The decision by the patients to disclose traditional and complementary medicine (TCM) use to their doctor is an important area to be explored.This study aimed to determine the disclosure of TCM use and its associated factors to medical doctor among primary care clinic attendees in Kuching Division, Sarawak. It was a cross-sectional study using questionnaire, interviewer administered questionnaire. A total of 1130 patients were screened with 80.2% reporting using TCM. Logistic regression analysis revealed that being female (AOR = 3.219, 95% CI: 1.385, 7.481), perceived benefits that TCM can prevent complication of illness (AOR = 3.999, 95% CI: 1.850, 8.644) and that TCM is more gentle and safer (AOR = 4.537, 95% CI: 2.332, 8.828), perceived barriers of not having enough knowledge about TCM (AOR = 0.530, 95% CI: 0.309, 0.910), patient dissatisfaction towards healthcare providers being too business-like and impersonal (AOR = 0.365, 95% CI: 0.199, 0.669) and paying more for healthcare than one can afford (AOR = 0.413, 95% CI: 0.250, 0.680), and accessibility of doctors (AOR = 3.971, 95% CI: 2.245, 7.023) are the predictors of disclosure of TCM use. An open communication between patients and doctor is important to ensure safe implementation and integration of both TCM and medical treatment.